Coexistence of obesity and unhealthy cardiorespiratory fitness in a cohort of boys - Nassis, George P.; Figueiredo, Pedro (International Journal of Sports Medicine, 2024)
The aim of the present study was to examine: 1) the coexistence of excessive body weight and low cardiorespiratory fitness (CRF), at a level to be considered unhealthy, and 2) the stability (tracking) of this profile. 1754 European boys, aged 8- to 14-years old, were tested for CRF and based on international cut points were classified as having healthy (H) or unhealthy (UN) CRF. Based on BMI they were classified as having normal weight (N), or overweight or obesity (OO). Chi-square was performed with four groups (i.e. N/H, N/UN, OO/H and OO/UN) and the odds ratios were calculated (cross-sectional analysis). A sub-group of 353 boys were followed for an average of 3.79±0.83 years (range: 2.97− 6.06; longitudinal analysis). The odds that a boy was with OO/UN profile compared to the normal body weight category ranged from 2.67 (13-years old) to 6.74 (9-years old). 56.6% of the participants remained in the same category, whereas 28.0% of them had ≥1 change in category to worst in the second assessment (Cohen Kappa= 0.557, p<0.001; substantial agreement). The odds ratios of having boys with unhealthy profile of combined excessive body weight and low CRF ranged from medium to large. The stability of unhealthy profile was substantial.
Keywords: obesity; fitness; children